Physiological and biochemical characteristics of the ethyl tiglate production pathway in the yeast Saprochaete suaveolens. Issue 1 (17th December 2014) - Grondin, Eric; Shum Cheong Sing, Alain; Caro, Yanis; de Billerbeck, Gustavo M.; François, Jean Marie; Petit, Thomas
Abstract A yeast identified as Saprochaete suaveolens was investigated for its capacity to produce a large panel of flavouring molecules. With a production of 32 compounds including 28 esters, S. suaveolens seems to be a good producer of fruity flavours and fragrances and especially of unsaturated esters, such as ethyl tiglate. Physiological and biochemical analyses were performed in this study in an attempt to comprehend the metabolic route to the formation of this compound. We show that the accumulation of ethyl tiglate by S. suaveolens is specifically induced by isoleucine. However, and contrary to S. cerevisiae, which harbours a classical Ehrlich pathway leading to the production of 2‐methylbutanol from isoleucine, our results provide phenotypic and enzymological evidence of ethyl tiglate biosynthesis in S. suaveolens through the catabolism of this amino acid by the β‐oxidation pathway, which generates tiglyl‐CoA as a probable intermediate. A kinetic analysis of this flavour molecule during growth of S. suaveolens on glucose and isoleucine showed a phase of production of ethyl tiglate that culminated concurrently with isoleucine exhaustion, followed by a disappearance of this compound, likely due to reassimilation by the yeast. Copyright © 2014 John Wiley & Sons, Ltd.